Hunter killer [videorecording (DVD)] - Butler, Gerard, 1969-; Oldman, Gary; Common (Musician); Cardellini, Linda, 1975- (Lionsgate, 2019)
An untested American submarine captain teams with US Navy SEALs to rescue the Russian president, who has been kidnapped by a rogue general.